Bilateral and ipsilateral asymmetries in lower body strength: A comparison of professional and Under-17 female soccer players - Parpa, K.; Giannou, E.; Michaelides, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Although the risk of injury in soccer is multifactorial, the lower-limb strength, anterior-posterior balance and inter-limb asymmetries should be monitored for both performance and injury prevention purposes. Soccer players have shown differences in strength between the dominant and non-dominant limbs, which may be due to the technical elements performed during the games and training. Therefore, this study examined the lower-limb strength, bilateral and ipsilateral asymmetries in professional and Under-17 female soccer players.